Pengaruh Perceived Value Terhadap Customer Identification dengan Dimediasi Customer Satisfaction pada Store Brand Indomaret - Adi Ghiffari Pratama; Muhammad Irfan Zaid; Yeni Nurmalasari (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purposive of this study is to test and analyze the influence between the perceived value to customer identification mediated by customer satisfaction on Indomaret Store Brand in Maranatha Christian University Bandung. This research uses causal explanatory research, with the population taken is students of economic faculty of Maranatha Christian University who shop at minimarket Indomaret in bandung city. Nonprobability sampling method used is the purposive sampling. Aquisition of primary data can be done by distributing questionnaires to consumers who researched to be respondent. Tecnique of data analysis uses path analysis. Based on the hypothesis test, researchers found the existence of significant influence between the perceived value towards customer satisfaction of 0.389, perceived value against the identification of 0.578, and the perceived value against customer identification mediated by customer satisfaction of 0.089.